Use of Nasal Airflow-Inducing Maneuver with olfactory training in patients with post-laryngectomy anosmia: a pilot study. (2nd January 2022) - St. Peter, Madeleine; Shankar, Suraj; Villwock, Jennifer
ABSTRACT: Up to 75% of patients who have undergone a total laryngectomy (TL) suffer from hyposmia or anosmia. The only intervention currently available is the Nasal Airflow-Inducing Maneuver (NAIM), which has been shown to restore smell in about half of TL patients with olfactory deficiencies. Although the NAIM can intermittently provide some mechanical compensation for olfactory loss, there are no therapeutic tools available that consistently provide olfactory stimulation and sensitization after TL. Olfactory training (OT) is a structured smell regimen that has been shown to recover smell in other patient populations with olfactory dysfunction such as post-viral and traumatic brain injury-induced anosmia. Our objective was to propose a low-cost, simple olfactory regimen for TL patients that combines OT and NAIM. In addition, we evaluate for changes in olfactory acuity using Sniffin' Sticks 12 (SST12) and QOL following training. Seven TL patients underwent NAIM training, baseline olfactory testing, and QOL assessments. Five participants completed the 12–14 week training regimen and had repeat olfactory and QOL testing. Two of the five participants had improved SST12 scores, however, QOL scores remained similar to baseline.